Effect of gamma sterilization on the properties of microneedle array transdermal patch system. (2nd April 2020) - Swathi, Honnavar Parthasarathy; Anusha Matadh, Vishwanath; Paul Guin, Jhimli; Narasimha Murthy, Sathyanarayana; Kanni, Paranjothy; Varshney, Lalit; Suresh, Sarasija; Shivakumar, Hagalavadi Nanjappa
Abstract: Soluble microneedles (MNs) of four different hydrophilic polymers namely sodium carboxymethyl cellulose ( CMC), polyvinylpyrrolidone (PVP) K30, PVP K90 and sodium hyaluronate (HU) were fabricated by mold casting technique. When exposed to gamma radiation, a dose of 25 kilogray (kGy) was found to render the microneedle (MN) sterile. However, CMC was found to form MNs with poor mechanical properties, whereas PVP K30 MNs were drastically deformed upon exposure to applied dose as observed in bright field microscopy. Scanning electron microscopy (SEM) revealed that morphology of PVP K90 and HU MNs were not significantly affected at the applied dose. The appearances of characteristic peaks of irradiated MNs of PVP K90 and HU in Fourier-transform infrared spectra suggested structural integrity of the polymers on irradiation. Differential scanning calorimetry (DSC) indicated gamma irradiation failed to alter the glass transition temperature and thus mechanical properties of PVP K90 MNs. However, DSC and Powder X-ray Diffraction (PXRD) conclusively indicated that the degree in crystallinity of HU was substantially reduced on irradiation. In vitro dissolution profiles of sterile PVP K90 and HU MNs were similar to un-irradiated MNs with a similarity factor ( f2 ) of 64 and 54, respectively. In vivo dissolution studies in human subjects indicated that sterile MNs of PVP K90 and HU exhibited dissolution of 78.45 ± 1.09 and 78.57 ± 0.70%, respectively, after 20 min. The studies suggested that PVP K90 and HU could be suitable polymers to fabricate soluble MNs as the structural, morphological, microstructural and dissolution properties remained unaltered post γ sterilization.